The effect of diet on the metabolism of N-6 and N-3 fatty acids in African vervet monkeys - Van Rooyen, Jacques (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1993.